Development and Implementation of Computerized Clinical Guidelines: Barriers and Solutions - Trivedi, M. H.; Kern, J. K.; Marcee, A.; Grannemann, B.; Kleiber, B.; Bettinger, T.; Altshuler, K. Z.; McClelland, A. (Methods of Information in Medicine, 2002)
Next, the article discusses the need to incorporate the use of surveys, questionnaires, or rating instruments for the collection of end-user feedback during and after the implementation process. A description of the types of rating instruments that will facilitate the assessment of user satisfaction is provided. Initial results from physician feedback during the implementation of our prototype are discussed. Research indicates that computerized decision support systems (CDSSs) can improve clinical performance and patient outcomes, and yet CDSSs are not in widespread use. Physician guidelines, in general, face barriers in implementation. Guidelines in a computerized format can overcome some of the barriers to conventional text-form guidelines; however, computerized programs have novel aspects that have to be considered, aspects such as technical problems/support and user interface issues that can act as barriers. Though the literature points out that human, organizational, and technical issues can act as barriers in the implementation of CDSSs, studies clearly indicate that there are methods that can overcome these barriers and improve CDSS acceptance and use. These methods come from lessons learned from a variety of CDSS implementation ventures. Notably, most of the methods that improve acceptance and use of a CDSS require feedback and involvement of end-users. Measuring and addressing physician or user attitudes toward the computerized support system has been shown to be important in the successful implementation of a CDSS. This article discusses: 1) the barriers of implementation of guidelines in general and of CDSSs; 2) the importance of the physician’s role in development, implementation, and adherence; 3) methods that can improve CDSS acceptance and use; and 4) the types of tools needed to obtain end-user feedback.
Keywords: Medical informatics; decision making; computer assisted; practice guidelines; communication barriers